2000
DOI: 10.1021/bi9927235
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Retinyl Esters by Pancreatic Triglyceride Lipase

Abstract: Previously [van Bennekum, A. M., et al. (1999) Biochemistry 38, 4150-4156] we showed that carboxyl ester lipase (CEL)-deficient (CELKO) mice have normal levels of pancreatic, bile salt-dependent retinyl ester hydrolase (REH) activity. In the present study, we further investigated this non-CEL REH activity in pancreas homogenates of CELKO and wild-type (WT) mice, and rats. REH activity was detected in both the presence and absence of tri- and dihydroxy bile salts in rats, WT mice, and CELKO mice. In contrast, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…This selectivity of trihydroxylated bile salt for TAG hydrolytic activity in PTL Ϫ/Ϫ pancreas is consistent with the trihdroxy-but not dihydroxy-bile salt dependence of CEL (6), thus implying that CEL may have a previously unrecognized role as a supplementary enzyme for TAG digestion in vivo. Likewise, significant colipase-dependent retinyl ester hydrolytic activity was demonstrated in pancreatic extracts from both CEL ϩ/ϩ and CEL Ϫ/Ϫ mice (7). This colipase dependence suggests that PTL may also serve as a retinyl ester hydrolase in the digestive tract.…”
mentioning
confidence: 85%
“…This selectivity of trihydroxylated bile salt for TAG hydrolytic activity in PTL Ϫ/Ϫ pancreas is consistent with the trihdroxy-but not dihydroxy-bile salt dependence of CEL (6), thus implying that CEL may have a previously unrecognized role as a supplementary enzyme for TAG digestion in vivo. Likewise, significant colipase-dependent retinyl ester hydrolytic activity was demonstrated in pancreatic extracts from both CEL ϩ/ϩ and CEL Ϫ/Ϫ mice (7). This colipase dependence suggests that PTL may also serve as a retinyl ester hydrolase in the digestive tract.…”
mentioning
confidence: 85%
“…Since tetrahydrolipstatin inhibits PTL as well as CEL, these results did not conclusively demonstrate the participation of CEL in vitamin absorption. In fact, earlier studies suggested that the PTL has retinyl ester hydrolytic activity (106). A third enzyme with the potential to contribute to vitamin A ester digestion and absorption is the intestinal phospholipase B. Rigtrup and Ong demonstrated that both CEL and phospholipase B are potent retinyl ester hydrolases and can be distinguished by their location either proximally or distally in the intestine, respectively (59,60).…”
Section: Vitamin Absorptionmentioning
confidence: 99%
“…Amino acid sequence alignments for previously reported human (Homo sapiens) PTL [56], PLR1 [61], PLR2 [6] and PLR3 [9] and mouse PTL [42,62], PLR1 [61] and PLR2 [26,42] sequences are shown in Figure 2 (also see 1). The amino acid sequence for the human PLR1 subunit contained 467 residues while the mouse PLR1 sequence contained 473 amino acids, due to an extended C-terminus sequence.…”
Section: Alignments Of Vertebrate Ptl-like Amino Acid Sequencesmentioning
confidence: 98%
“…These overall features are readily observed for the predicted frog PTL and PLR1 three-dimensional structures. Table 1 and Supplementary Table 1 summarize the predicted locations for vertebrate PTL-like genes based upon BLAT interrogations of genomes using the reported sequences for human PTL, PLR1, PLR2 and PLR3 [6,9,56,61] and the predicted sequences for other vertebrate PTL-like proteins and the UC Santa Cruz Genome Browser [49]. The mammalian PTL-like genes were predominantly transcribed on the positive strand and located in the following gene order: PLR3-PTL-PLR1-PLR2 for human (see Supplementary Figure 2), orangutan and rhesus genomes; and PTL-PLR1-PLR2 for other mammalian genomes, including mouse, rat, dog, pig, rabbit, opossum and platypus genomes (Table 1 and Supplementary Table 1).…”
Section: Secondary and Tertiary Structures For Vertebrate Ptl-like LImentioning
confidence: 99%